Novel Thiosemicarbazones Sensitize Pediatric Solid Tumor Cell-Types to Conventional Chemotherapeutics through Multiple Molecular Mechanisms - Paukovcekova, Silvia; Skoda, Jan; Neradil, Jakub; Mikulenkova, Erika; Chlapek, Petr; Sterba, Jaroslav; Richardson, Des R; Veselska, Renata (Cancers, 2020)
Combining low-dose chemotherapies is a strategy for designing less toxic and more potent childhood cancer treatments. We examined the effects of combining the novel thiosemicarbazones, di-2-pyridylketone 4-cyclohexyl-4-methyl-3-thiosemicarbazone (DpC), or its analog, di-2-pyridylketone-4,4-dimethyl-3-thiosemicarbazone (Dp44mT), with the standard chemotherapies, celecoxib (CX), etoposide (ETO), or temozolomide (TMZ). These combinations were analyzed for synergism to inhibit proliferation of three pediatric tumor cell-types, namely osteosarcoma (Saos-2), medulloblastoma (Daoy) and neuroblastoma (SH-SY5Y). In terms of mechanistic dissection, this study discovered novel thiosemicarbazone targets not previously identified and which are important for considering possible drug combinations. In this case, DpC and Dp44mT caused: (1) up-regulation of a major protein target of CX, namely cyclooxygenase-2 (COX-2); (2) down-regulation of the DNA repair protein, O6-methylguanine DNA methyltransferase (MGMT), which is known to affect TMZ resistance; (3) down-regulation of mismatch repair (MMR) proteins, MSH2 and MSH6, in Daoy and SH-SY5Y cells; and (4) down-regulation in all three cell-types of the MMR repair protein, MLH1, and also topoisomerase 2α (Topo2α), the latter of which is an ETO target. While thiosemicarbazones up-regulate the metastasis suppressor, NDRG1, in adult cancers, it is demonstrated herein for the first time that they induce NDRG1 in all three pediatric tumor cell-types, validating its role as a potential target. In fact, siRNA studies indicated that NDRG1 was responsible for MGMT down-regulation that may prevent TMZ resistance. Examining the effects of combining thiosemicarbazones with CX, ETO, or TMZ, the most promising synergism was obtained using CX. Of interest, a positive relationship was observed between NDRG1 expression of the cell-type and the synergistic activity observed in the combination of thiosemicarbazones and CX. These studies identify novel thiosemicarbazone targets relevant to childhood cancer combination chemotherapy.
Keywords: medulloblastoma; temozolomide; etoposide; thiosemicarbazones; celecoxib; DpC; Dp44mT; neuroblastoma; combined anti-cancer treatment; osteosarcoma